O clube no coração e/ou no bolso: os processos de mercantilização do torcer a partir de um programa de sócio torcedor - Thiago Jose Silva Santana (2016)
Over time football has undergone numerous changes influenced by various events that have altered the way it is managed and also how it is experienced. Consequently, the relations between those involved with the sport have also changed. Among these changes are the relationship between the supporters and the club. One of the phenomena that have been modifying this relationship is the emergence of the fan membership program. The aim of this study was to analyze the relationship that supporters of Clube Atlético Mineiro establish with the fan membership program. Specifically sought to identify the socioeconomic profile of frequenters of the games, their opinion about the fan membership program, relations that supporters have with this program and how the club understands the relationship with their supporters, participant or not of its fan membership program. For that, a bibliographical, documentary and fieldwork survey was carried out. Bibliographical research consisted of the search for academic papers that approached the phenomenon of the supportive member. Documentary research analyzed laws, match reports and the program's website. Fieldwork consisted of the analysis of the data of 435 questionnaires collected in five games of the Brazilian Championship of 2016, of which 286 are members of the fan membership program and 149 are non-members. There were also interviews with supporters members, non-members and a manager of the fan membership program, the Galo na Veia. After analysis, results showed that the profile of the members is composed of men, singles, young people, with higher education level, professionally allocated in the private sector, residents of Belo Horizonte and using their own vehicle to go to the stadium. It was identified that the program has in general, a significant acceptance by the supporters although they have little knowledge about the program, focusing mainly on the issue of access to the stadium. Data also showed that the fan membership program has modified the relationship between supporters and club and is set as a symbol of distinction between fans. The understanding of the relationship between the club and its fans is guided by a business logic, whose model of connection with the supporter was based on the process of commodification of support established in other countries. The commodification process of support ends up limiting this experience to a narrow group, removing those who cannot afford the values that this logic requires. This research may also promote the reflection of club program managers so that they can mediate the club's economic interests without the summary exclusion of low-income supporters.